Exercise and Cancer Survivorship Impact on Health Outcomes and Quality of Life - Saxton, John.; Daley, Amanda; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
An increasing number of people are now surviving for longer periods of time after a cancer diagnosis due to effective screening programs and treatments. In 2008, 25 million people were either living with cancer or recovering from cancer treatment worldwide. This means that the quality of cancer survival has become an important issue in the management of cancer patients. The cancer experience is widely acknowledged as a life-changing event and can be the trigger for reviewing personal health behaviours and making major lifestyle changes. Evidence suggests that regular exercise participation during and after cancer treatment is associated with higher levels of physical functioning, reduced feelings of fatigue and improved health-related quality of life. Studies have also shown that a physically active lifestyle can protect against cancer mortality. Exercise and Cancer Survivorship: Impact on Health Outcomes and Quality of Life explores the impact of a physically active lifestyle on health outcomes that are highly relevant to cancer patients at all stages of the cancer experience. Twelve active and eminent researchers or research groups in this field from the USA, Canada and Europe present an up-to-date synthesis of the scientific evidence. We hope that the book will provide an impetus for further research in the field, so that ultimately, all cancer patients will have the opportunity to experience the benefits that exercise might have to offer to them.
Exercise and Cancer-Related Fatigue Syndrome -- Exercise as an Intervention During Breast Cancer Treatment -- Exercise After Treatment for Breast Cancer: Effects on Quality of Life -- The Importance of Controlling Body Weight After a Diagnosis of Breast Cancer: The Role of Diet and Exercise in Breast Cancer Patient Management -- The Biological Mechanisms by Which Physical Activity Might Have an Impact on Outcome/Prognosis After a Breast Cancer Diagnosis -- Exercise After Prostate Cancer Diagnosis -- Exercise for Prevention and Treatment of Prostate Cancer: Cellular Mechanisms -- Physical Activity Before and After Diagnosis of Colorectal Cancer -- Exercise-Based Rehabilitation in Patients with Lung Cancer -- Exercise and Cancer Mortality -- Ready to Change Lifestyle? The Feasibility of Exercise Interventions in Cancer Patients -- Cardiorespiratory Exercise Testing in Adult Cancer Patients.
Keywords: Medicine; Oncology; Toxicology; Biomedicine; Cancer Research; Pharmacology/Toxicology.